Coming to painting. (1st April 2017) - Talbot, Emma
This article is a response to Sunil Manghani's article 'Painting as commitment', and its opening discourse, allying 'commitment' in painting to Sartre's notion of a committed writer. In the light of Manghani's reference to the writing of Hélène Cixous, this article seeks to draw comparisons between Hélène Cixous's meditations on and approaches to writing with a personal account of approaching painting. In particular, this article will look at the issue of painting from personal experience and the intimate as material for making work.